2012
DOI: 10.1111/j.1525-139x.2012.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula Creation Using the Optiflow Vascular Anastomosis Device: A First in Man Pilot Study

Abstract: Although arteriovenous fistulae are the preferred form of dialysis vascular access they continue to have significant problems with maturation failure. The Optiflow device is a sutureless anastomotic conduit which could potentially reduce surgical time and also standardize the surgical procedure. We report herein on the "First in Man" experience with the Optiflow device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Applying local interventions which reduce vascular injury, improve shear stress‐induced vasodilation, promote outward remodeling and inhibit neointimal hyperplasia formation may be more innovative and effective. Such interventions include the use of new surgical techniques to alter wall shear stress, endovascular access creation, far infrared therapy, paclitaxel‐coated balloon angioplasty, and perivascular application of recombinant elastase, endothelial loaded gel foam wrap (Vascugel) or antiproliferative agents such as sirolimus (Coll‐R) . Table provides an overview of mode of action and expected outcomes of these local and novel interventions that predominantly prevent vascular injury, modulate the response to vascular injury and/or promote outward remodeling rather than targeting thrombosis prevention.…”
Section: Novel and Future Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying local interventions which reduce vascular injury, improve shear stress‐induced vasodilation, promote outward remodeling and inhibit neointimal hyperplasia formation may be more innovative and effective. Such interventions include the use of new surgical techniques to alter wall shear stress, endovascular access creation, far infrared therapy, paclitaxel‐coated balloon angioplasty, and perivascular application of recombinant elastase, endothelial loaded gel foam wrap (Vascugel) or antiproliferative agents such as sirolimus (Coll‐R) . Table provides an overview of mode of action and expected outcomes of these local and novel interventions that predominantly prevent vascular injury, modulate the response to vascular injury and/or promote outward remodeling rather than targeting thrombosis prevention.…”
Section: Novel and Future Treatment Strategiesmentioning
confidence: 99%
“…| 253 neointimal hyperplasia formation may be more innovative and effective. Such interventions include the use of new surgical techniques to alter wall shear stress,96 endovascular access creation, 97 far infrared therapy, 98,99 paclitaxel-coated balloon angioplasty, 100,101 and perivascular application of recombinant elastase, 102,103 endothelial loaded gel foam wrap (Vascugel)…”
mentioning
confidence: 99%
“…The Optiflow™ device has been the most studied; in a human pilot study safety and technical success were achieved in 10 patients [226]. A follow up study of 41 patients showed unassisted patency of 78% at 90 days with no device related adverse events [227].…”
Section: Future Approaches To Treatmentmentioning
confidence: 99%
“…Optiflow Anastomotic Connector. This is a sutureless anastomotic connector being developed primarily for AVF creation, which also has the potential to be used for creating a graft-vein anastomosis (93). In addition to reducing surgical time and to some extent leveling the playing field with regard to surgical skill, the ''Optiflow'' connector may favorably alter the anatomical configuration at the graft-vein anastomosis and improve the hemodynamic shear stress profile at this site ( Fig.…”
Section: Special Devices and Bioengineered Vesselsmentioning
confidence: 99%